2012
DOI: 10.3899/jrheum.110919
|View full text |Cite
|
Sign up to set email alerts
|

Construct Validity of the Modified Numeric Rating Scale of Patient Global Assessment in Psoriatic Arthritis

Abstract: Judged on an NRS, the PGA had good construct validity and satisfactorily distinguished all levels of severity in PsA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 19 publications
(21 reference statements)
0
11
0
1
Order By: Relevance
“…Husted 1996 (5) 39 Husted 1996 40 Duffy 1992 41 46 Kwok 2010 31 Leung 2012 47 Dandorfer 2012 7 Peripheral joint activity…”
Section: Aimsmentioning
confidence: 99%
“…Husted 1996 (5) 39 Husted 1996 40 Duffy 1992 41 46 Kwok 2010 31 Leung 2012 47 Dandorfer 2012 7 Peripheral joint activity…”
Section: Aimsmentioning
confidence: 99%
“…Additional important domains include enthesitis, dactylitis, fatigue, nail disease, spinal disease, acute‐phase reactant, and physician global assessment (PhGA). PtGA was found to be a reliable tool for assessing skin and joint disease activity among patients with PsA (). However, since the scores of the skin and joint often diverge, it was suggested that each of these domains should be scored separately ().…”
Section: Introductionmentioning
confidence: 99%
“…In the univariable analysis, we presented the Spearman's Rho correlations for variables with both PGA and PhGA; and the discordance (PGA‐PhGA). Based on previous studies, we hypothesized that PGA would have strong correlations with pain and physical function but moderate correlation with joint count . We also expected strong correlations to exist between PhGA and joint count.…”
Section: Methodsmentioning
confidence: 91%
“…Nonetheless, PGA‐PhGA did not seem to be related to follow‐up times in our sensitivity analysis. We did not assess PGA separately for skin vs arthritis, but from a previous study, PGA should represent more arthritis than skin, particularly in a cohort with low median PASI. Moreover, we did not collect data and therefore cannot account for chronic widespread pain syndromes and fibromyalgia which are well‐known to have large effects on pain and PGA, and theoretically may have less impact on PhGA.…”
Section: Discussionmentioning
confidence: 99%